Mitochondrial Respiratory Capacity is Restored in Hibernating Cardiomyocytes Following Co-Culture with Mesenchymal Stem Cells. (4th March 2019) - Stone, Laura L. Hocum; Chappuis, Erin; Marquez, Maribel; McFalls, Edward O; Kelly, Rosemary F.; Butterick, Tammy
Hibernating myocardium is a subset of ischemic cardiac disease characterized by viable but dysfunctional tissue. Standard treatment for hibernating myocardium is coronary artery bypass graft, which reduces arrhythmias and improves survival but does not fully restore function, presenting a gap in currently available treatments. Large animal studies of hibernating myocardium have identified impaired mitochondrial dynamics as a root cause of persistent cardiac dysfunction despite surgical revascularization. This study presents a novel in vitro model of hibernating myocardium cardiomyocytes to study active mitochondrial respiration in hibernating myocardium cells, and to test the paracrine effect of mesenchymal stem cells on impaired mitochondrial function. Exposure of cardiomyocytes to hypoxic conditions of 1% oxygen for 24 hours resulted in a phenotype consistent with hibernating myocardium cardiac tissue, including decreased respiratory capacity under high work states, decreased expression of mitochondrial proteins, and preserved cellular viability. Co-culture of hibernating myocardium cardiomyocytes with mesenchymal stem cells restored mitochondrial respiratory function, potentially via an increase in proliferator-activated receptor gamma coactivator 1-alpha-driven mitochondrial biogenesis. Co-culture treatment of hibernating myocardium cardiomyocytes with mesenchymal stem cells shows improvement in both mitochondrial function and ATP production, both of which are critical for effectively functioning cardiac tissue. These results suggest that mesenchymal stem cell therapy as an adjunct treatment to revascularization may address the current gap in treatment for hibernating myocardium patients.